Non-puerperal uterine inversion due to huge submucosal uterine myoma: a case report - Amadi, Simeon C.; Awoyesuku, Peter A.; Altraide, Basil O. A.; Ohaka, Chinweowa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Uterine inversion is a rare clinical entity with challenging diagnosis and management. Reports of successfully managed cases contribute to knowledge and aid future management of cases among practitioners. We report a case of a 46 year old para-3 with protrusion of a mass from her vagina and vaginal bleeding of 7 days duration. She was managed as a case of chronic uterine inversion. She was resuscitated and had vaginal myomectomy, Haultin’s procedure and subsequently total abdominal hysterectomy due to ischaemic necrosis of parts of the uterus.